Pemberdayaan Kelompok Tani Pincuran Gadang melalui Inovasi Pemasaran Digital untuk Meningkatkan Daya Saing Usaha Kambing Potong - Rahmi Awalina; Tevina Edwin; Wellyalina Wellyalina (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Pincuran Gadang Farmers Group, a part of the BUMNag Balai Panjang enterprise in Lareh Sago Halaban District, Lima Puluh Kota Regency, faced the problem of low sales performance in its Jawarandu goat business due to a conventional marketing approach. Over the past year, the group’s average sales reached only two to three goats per month, mainly relying on word-of-mouth and limited Facebook promotion. This community service program aimed to enhance the group’s income and business competitiveness through the implementation of a hybrid marketing strategy combining conventional and digital promotion methods. The activities included field observation, participatory mentoring, the creation of printed brochures for goat marketing, and the development of an official Instagram account as a digital promotion tool. The results indicated improvements in members’ understanding and skills in managing promotional media, stronger business branding, and increased interaction with potential customers within and beyond the local community. Furthermore, the adoption of digital marketing expanded the group’s market reach and improved consumer trust in local livestock products. The integration of printed and digital promotion proved to be an effective approach to strengthening the economic independence of smallholder livestock farmers while fostering the community’s digital capacity. The sustainability implication of this program lies in the establishment of a sustainable community marketing model that can be replicated by other rural farmer groups to promote inclusive and resilient agribusiness development.